first, we have to balance the equation:
Al + H2SO4 → Al2(SO4)3 + H2
we have the number of Al atoms not equal on both sides so we will put 2 Al instead of Al on the left side of the equation.
2Al + H2SO4 → Al2(SO4)3 + H2
now we have an unequal number of (SO4) group on both sides of the equation so we put 3H2SO4 instead of H2SO4
2Al + 3H2SO4 → Al2(SO4)3 + H2
now, we have to put 3H2 instead of H2 to make the H atoms equals on both sides.
2Al + 3H2SO4 → Al2(SO4)3 + 3H2 this is the final balanced equation.
∴ the coefficient of H2SO4 is 3